1998
DOI: 10.1007/s002130050711
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxytryptamine receptor function in humans is reduced by acute administration of hydrocortisone

Abstract: 5-Hydroxytryptamine1A (5-HT1A) receptors have been shown to be suppressed by corticosteroid hormones in a variety of animal experimental paradigms. It has been suggested that this effect may be central to the pathophysiology of severe clinical depressive illness, a condition in which 5-HT1A receptor function is reduced and corticosteroid hormones are elevated. We report the effects of acute administration of hydrocortisone in normal volunteers on a neuroendocrine model of 5-HT1A receptor function. Fifteen heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 38 publications
4
26
0
Order By: Relevance
“…This response was not attenuated by hydrocortisone pre-treatment, although the TSH response to TRH was blunted. This finding is in accord with our previous work showing that an acute dose of hydrocortisone (100 mg, 11 h prior) attenuates the GH response to l-TRP in healthy volunteers (Porter et al 1998) and would seem to support the hypothesis that the function of the 5-HT 1A receptor is reduced by glucocorticoid administration. However, an alternative explanatory mechanism is that hydrocortisone acts at the pituitary level to inhibit GH response.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This response was not attenuated by hydrocortisone pre-treatment, although the TSH response to TRH was blunted. This finding is in accord with our previous work showing that an acute dose of hydrocortisone (100 mg, 11 h prior) attenuates the GH response to l-TRP in healthy volunteers (Porter et al 1998) and would seem to support the hypothesis that the function of the 5-HT 1A receptor is reduced by glucocorticoid administration. However, an alternative explanatory mechanism is that hydrocortisone acts at the pituitary level to inhibit GH response.…”
Section: Discussionsupporting
confidence: 90%
“…Our previous finding of a reduced GH response to l-TRP following acute pre-treatment with hydrocortisone (Porter et al 1998) could also be explained by an effect of hydrocortisone at the pituitary level. Studies that have examined hormonal responses to l-TRP in depressed patients have found that, after controlling for confounding factors such as weight loss and absolute TRP levels, both GH and PRL are blunted (Power and Cowen 1992), suggesting an attenuation in 5-HT 1A receptor function.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Also, CRF acts on locus ceruleus and raphe nuclei and regulates production of NA, a transmitter thought to be of importance in depression [113]. Further supporting a link between depression and HPA-axes dysfunction are the findings that high circulating levels of cortisol reduce the number of post-synaptic 5-HT 1A -receptors, consistent with increased depressive symptoms [117]. On the other hand, short pulses of increased corticosteroids may up-regulate somatodendritic levels of 5-HT 1A -receptors in a way potentially protecting against depression [118][119][120], and short term infusion of high doses of corticosteroids may result in hypomania, not depression.…”
Section: Hpa-axesmentioning
confidence: 99%
“…The elevation of cortisol and prolactin secretion following an acute fenfluramine challenge is also reduced in patients with depression [26] . In regard to changes in serotonin receptor function in depressed patients, there is clinical evidence that the secretion of growth hormone in response to tryptophan is attenuated by pre-treatment with the naturally occurring glucocorticoid hydrocortisone but, somewhat surprisingly, not the synthetic glucocorticoid dexamethasone [27] .…”
Section: The Hpa Axis and Serotoninmentioning
confidence: 99%